Iterative stochastic subspace self-consistent field method - Loos, Pierre-François; Jean-Louis Rivail; Assfeld, Xavier (arXiv.org, 2021)
We propose a new self-consistent field (SCF) algorithm based on an iterative, partially stochastic \textit{``Divide & Conquer''}-type approach. This new SCF algorithm is a simple variant of the usual SCF procedure and can be easily implemented in parallel. A detailed description of the algorithm is reported. We illustrate this new method on one-dimensional hydrogen chains and three-dimensional hydrogen clusters.